What criterion should define African philosophy - Peter Bisong Bisong (International Journal of Humanities and Innovation (IJHI), 2020)
The question of what criterion is to be used to map out African from non-African philosophy has occupied the minds of scholars for some time now. The debate wax stronger and unfortunately, I am drafted to it now. My decision to join the debate is due to the perceived importance of getting the criterion for African philosophy right. A faulty criterion would amount to a weakened foundation for African philosophy. It would also set the stage for a bleak future for African philosophy. This research using the philosophical method of critical analysis, examined the many proposed criteria for African Philosophy and found them wanting and on the heels of that, set a criterion that would overcome their limitations.